Design study of a pyrolysis plant compressor with heavy wall erosion from metal particle impact - Omri, Riadh; Semel, Matthias; Delgado, Antonio; Rußwurm, Hans (Proceedings of the ASME 2017 Fluids Engineering Division Summer Meeting. Volume 1A, Symposia: Keynotes; Advances in Numerical Modeling for Turbomachinery Flow Optimization; Fluid Machinery; Industrial and Environmental Applications of Fluid Mechanics, 2017)
In a pyrolysis plant, a mounted centrifugal compressor takes heavy damage because of erosion originating from metal particle mixed with the inlet air flow impacting its blades and volute walls. In a first step, the original impeller design as well as other centrifugal compressor designs are studied to identify the design parameters which influence the erosion distribution, shape and magnitude. It has been concluded that the first impact plays an important role in defining the particles trajectories and the erosion on the walls. A novel impeller design method based on particle trajectories after a controlled first impact is introduced. The new setup is simulated via CFD coupled with Finnie erosion model to assess the damage. This design is improved in a further step. Adequate simulation setups such as interfaces, boundary conditions and particle coupling methods with carrier fluid are introduced. This study focuses on predicting the particle trajectory within the impeller to reduce the impacts on blade walls and thus reducing the erosion rate. For all designs, the analysis is conducted in the same stage operating point, this point is defined at a predefined volume flow VF [kg/m3] and total-to-static pressure Δp[Pa] as is recommended for the pyrolysis facility including the compressor. Simulations are conducted in a steady state with compressible air at high static temperature going to 530°C. For CFD calculations the software in use is CFX of the ANSYS Group. All mesh used is structured and produced by TurboGrid for the blade rows and with Icem for inlet, outlet and volute. The final compressor design contain the design recommendation for hub form and outlet flow angle.

Study of heavy erosion damage in a radial air compressor with means of coupled CFD erosion simulation and experiment - Omri, Riadh; Schöneberger, Bastian; Delgado, Antonio; Rußwurm, Hans (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
In a pyrolysis plant, a mounted centrifugal fan takes heavy damage because of erosion origi-nating from metal particles mixed with the inlet air flow impacting its blades and volute walls. In a previous study a new design strategy has been undertaken to specifically overcome the excessive erosion damage on the blades resulting in a new design for the fan which has been investigated by means of CFD simulations coupled with a Finnie erosion model to as-sess the damage via ANSYS CFX. This study focuses on further qualitatively assessing the erosion model adopted previously. An available air-compressor in laboratory scale is investigated experimentally in similar con-ditions. Two layers of paint in different colors cover the walls of the rotor and the inside walls of the volute to better locate the damaged areas. The introduction of the metal particles is regulated via a rotary feeder installed for this purpose into the test setup. The experiments show the effect of the first impact of the particles and severe damages only to the pressure side of the rotor, the suction side is not affected. These results have been ob-served via CFD in beforehand. The analysis is conducted in the same chosen stage operating point, defined at a predefined volume flow VF [kg/m³] and total-to-static pressure Δp[Pa]. Simulations are conducted in steady state with compressible air at high static temperature going to 530°C. For CFD calcu-lations the software in use is CFX of the ANSYS Group. All mesh used is structured and pro-duced by TurboGrid and Icem for the different setup part
Keywords: numerical Simulation; Centrifugal fan; erosion modelling; pressure measurement